Incidence of Acute Kidney Injury in Asphyxiated Neonates and Its Relationship with Severity of Hypoxic-Ischemic Encephalopathy: Experience from a Medical College Hospital, Bangladesh. - Das, Ashith Chandra; Azad, Md Tarek; Dev, Archana; Dey, Taposi; Rahman, Zainab (Bangladesh Journal of Child Health, 2024)
Background: Perinatal asphyxia (PNA) is one of the leading causes of neonatal morbidity and mortality in Bangladesh. Among others, hypoxic-ischemic encephalopathy and acute kidney injury are two common complications of perinatal asphyxia. Morbidity and mortality increases when PNA is associated with these two complications. Objective: The objectives of the study were to determine the incidence of acute kidney injury (AKI) among asphyxiated neonates associated with various stages of hypoxic-ischemic encephalopathy (HIE) and to find out the relationship between AKI and HIE stages. Materials and Methods: This cross-sectional study was conducted in the neonatal unit of Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, between the periods of January 2018 and June 2018. A total of 130 newborns admitted in the neonatal ward within 24 hours of age with perinatal asphyxia and hypoxic-ischemic encephalopathy were included in the study by the consecutive sampling method. Serum creatinine level was measured at 24 hours after birth. AKI was considered if serum creatinine level was ³1.5 mg/dL. Result: Among 130 neonates, 35.4% had HIE stage-I, 56.1% had HIE stage-II and 8.5% had HIE stage-III. AKI was present in 12.3% of the asphyxiated neonates. There were no significant relationship between AKI and demographic variables like gender, birth weight, and place of delivery, mode of delivery and parity of the mothers. AKI was significantly associated with HIE stage-II and stage-III compared to HIE stage-I (p=0.02). The mean serum creatinine level was significantly higher in HIE stage-II and stage-III than HIE stage-I (p=0.001). Among the study neonates, 28.5% died. There was no significant relationship between death and AKI (p=0.74). The Pearson correlation test revealed no statistically significant relationship between serum creatinine levels and hospital stay. Conclusion: The incidence of acute kidney injury was 12.3% among asphyxiated newborn associated with HIE. Frequency of AKI significantly associated with severity of HIE. BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 24-29